A common risk variant in the MTHFR gene contributes to age‐related cerebrovascular dysfunction in VCID: Development of new models and analysis methods/novel assays and technologies. (7th December 2020) - Reagan, Alaina M.; Christensen, Karen; Haber, Annat; Rozen, Rima; Carter, Gregory W.; Sasner, Michael; Howell, Gareth
Abstract: Background: Cerebrovascular damage occurs during aging, Alzheimer's disease and Vascular Dementia, commonly referred to as Vascular Contributions to Cognitive Impairment and Dementia (VCID). However, few mouse models currently recapitulate human cerebrovascular deficiencies in disease. The C677T variant in methylenetetrahydrofolate reductase ( MTHFR C677T ) is commonly associated with VCID. MTHFR codes for an enzyme involved in production of folate, homocysteine, and methionine metabolism. The MTHFR C677T polymorphism is predicted to result in hyperhomocysteinemia, a condition that causes vascular inflammation and vascular damage. Additionally, methionine deficiency can result in DNA hypomethylation and has been confirmed in MTHFR C677T carriers. Despite the fact that, in some populations, MTHFR C677T is more common than APOE E4, mechanisms by which MTHFR C677T increases risk for VCID are not known. Methods: CRISPR technology was employed to engineer the Mthfr C677T allele into C57BL/6J (B6) mice. Vascular health is being assessed in 6, 12, 18 and 24 months‐old mice using leakage assays (FITC‐dextran and presence of extravascular fibrin) and immunofluorescence (IF) to examine blood brain barrier integrity in the cerebrovascular unit: endothelium (CD31) smooth muscle (aSMA) pericytes (PDGRFb) basement membrane (ColIV) and tight junctions (Claudin‐5, Occludin, ZO‐1). Functional MRI is used to determine in vivo vascular reactivity. Bulk RNA sequencing and Reduced Representation Bisulfite Sequencing (RRBS) were performed on half brains to assess differential gene expression and DNA methylation, respectively. Results: Mice with the Mthfr C677T risk variant have significantly reduced liver enzymatic activity, significantly increased plasma homocysteine levels and decreased methionine levels, recapitulating the human phenotype. Transcriptional profiling of brain tissue revealed genes regulating circadian rhythm, neurogenesis, ER stress and GABA signaling are differentially expressed (DE) in B6. Mthfr C677T compared to B6 samples. RRBS data demonstrated significant genome‐wide DNA hypomethylation in these mice. Hypomethylated and DE genes are expressed in astrocytes, microglia and endothelial cells and are predicted to regulate apoptosis/proliferation, inflammation and glucose transport across the blood brain barrier. Validation by IF is underway. Conclusion: We have created a novel mouse strain to determine the precise mechanisms by which MTHFR C677T increases risk for VCID. This work aims to identify novel therapeutic approaches that preserve cerebrovascular health throughout aging to prevent VCID.